Concept, architecture and key technologies of industrial internet - Jin QI; Wei WANG; Mengxi CHEN; Bin XU; Zhenjiang DONG; Yanfei SUN (物联网学报)
As one of the key paths to realize the digital transformation of traditional industries, the industrial internet has attracted widespread attention in both the academia and the industry.As the content of the industrial internet is quite extensive, while its system architecture and key technologies are constantly evolving and developing, it also confronts problems such as unclear conceptual scope, unsound system architecture, and unclear key technologies.In order to further explore the above issues, the basic concepts of the industrial internet were clarified by sorting the relationship between the industrial internet and three other concepts of the industrial internet of things, industry 4.0/5.0, and intelligent manufacturing.Based on the analysis of the industrial internet system architecture and the key technologies involved, the challenges faced by the industrial internet were summarized and the future research directions in the industrial internet field were looked forward.